Pengoptimalan Distribusi Barang pada Dua Depo PT. X dengan Dua Tipe Kendaraan yang Berbeda - Yosephine Tiffani Gondo (Jurnal Titra, 2016)
This study is a continuation of previous studies, by Lydia Yoanita research conducted in 2014 under title The Distribution Optimization Goods with N Vehicles with Two Depos. Problems solved by four alternative methods, and the results declared one of the methods chosen for the most optimal in terms of distance and time calculations. The advantage of this method is generating distance and time calculations are optimal. The downside of the four methods is use same assumptions, vehicle capacity is 130 gallons. This study focuses on the difference in the two types of vehicles of different capacities, 130 gallons and 108 gallons. The design is done by grouping the corresponding customer address using clustering methods and Clarke and Wright algorithm. Grouping is limited by the capacity of the vehicle that has been available at each depot. Results of this design is 12 divided by the delivery of two vehicle types and two different depos. These routes are said to be optimal when the vehicles reach maximum capacity and relatively close proximity to the depos.